2020
DOI: 10.1038/s41598-020-59113-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma as an adjuvant to surgical carpal ligament release: a prospective, randomized controlled clinical trial

Abstract: The purpose of this study is to evaluate the efficiency of local platelet-rich plasma (PRP) injection as an adjuvant treatment after carpal ligament release. We conducted a prospective randomized, tripleblinded, controlled trial. Fifty participants with mild to extreme carpal tunnel syndrome (CTS) were randomly assigned either to the PRP (n = 25) or the platelet-poor plasma (PPP, n = 25) group. After performing open surgical release of the carpal ligament, the inside of the carpal tunnel was irrigated with 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 89 publications
(83 reference statements)
2
14
0
Order By: Relevance
“…Three articles were identified for PRP use in hand surgery (1 level I and 2 level IV). 18 The level-I study was on the effect of PRP on the carpal tunnel release. Level-IV studies were on the use of PRP in the setting of amputation and in patients with basal thumb arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles were identified for PRP use in hand surgery (1 level I and 2 level IV). 18 The level-I study was on the effect of PRP on the carpal tunnel release. Level-IV studies were on the use of PRP in the setting of amputation and in patients with basal thumb arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…CTS usually occurs with repetitive movements of wrist and resulting in synovial sheath hypertrophy, tenosynovitis, intracarpal swelling and MN compression (1,15,16). Rheumatoid arthritis, scleroderma, systemic lupus erythematosus, polymyalgia rheumatica, collagen tissue diseases, diabetes mellitus, pregnancy, estrogen and oral contraceptive use, acromegaly, myxedema, hyperparathyroidism, amyloidosis, tumors such as lipoma and ganglioma, chronic trauma are diseases and conditions associated with CTS.…”
Section: Resultsmentioning
confidence: 99%
“…Carpal tunnel syndrome ( CTS ) is the most common peripheral nerve entrapment and is seen in 3% of the general population (1). The carpal tunnel ( CT ) is formed by the wrist bones, the transvers ligament ( TL ), exor retinaculum, and the median nerve ( MN ) passes into the CT (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another recent two nonblinded trials with very short-term follow-up (<10 weeks) reported inconsistent benefit of additional 1 mL PRP in patients with mild CTS treating wrist splint [ 45 , 47 ]. Trull-Ahuir et al [ 49 ] shared a randomized, triple-blind trial and shown significant improvement of hand grip strength at 6 th weeks in patient receiving surgical release of FR compared with platelet-poor plasma injection. The double-blind placebo-controlled study in 2021 had shown one-year efficacy of single-dose ultrasound-guided perineural injection with PRP in patients with moderate-to-severe CTS compared with NS injection [ 50 ].…”
Section: Novel Motor-sparing Neural Injection For Ctsmentioning
confidence: 99%